ENHANCING STUDENTS’ ACHIEVEMENT AND INTEREST IN SENIOR SECONDARY SCHOOL FINANCIAL ACCOUNTING , THROUGH COMPUTER ASSISTED INSTRUCTIONAL PACKAGE IN OGUN STATE - Kiadese, Adeola (Sokoto Educational Review, 2007)
This study tests the potency of the computer-assisted instructional package on students’ achievement and interest in Secondary School Financial Accounting. It adopted a pre-test, post-test control group design in a quasi-experimental setting. The study involved 105 Senior Secondary School II students selected through purposive sampling technique. Data were collected using 2 validated instruments. Financial Accounting Achievement Test (FAAT) and Financial Accounting Interest Scale (FAIS), which were analyzed using the t-test of significance at the .05 sig level. Findings from this study indicated a significant main effect of the treatment on students’ achievement and interest in favour of the experimental group. The results, however, proved that a computer-assisted instructional package is a powerful tool for enhancing students’ achievement and interest in Financial Accounting. Based on these findings the researcher recommends that government and all stakeholders in education should provide computers, programs, instructional packages and enabling environment for the implementation of computer-assisted instructions in schools.